O fenômeno da violência na lógica de reprodução do capital - Santos, Maricelly Costa (2014)
Addressing the phenomenon of violence in the logic of reproduction of capital, the present work aims by conducting a literature search, uncovering its material basis in capitalist society, starting the process of transition from feudal to the capitalist system and its consolidation with the Revolution industrial, demonstrating the violent intensified exploitation of labor by capital. Besides the economic character of the violence, we also seek to demonstrate how their extraeconomic character, which reaches the ideological dimension, appears in the monopoly stage of capitalism on ways of managing the workforce (implementation of Taylorism and Fordism Toyotism production models) that through a combination of control and coercion, seek to promote the involvement of labor in the production process capturing their subjectivity and putting it at the service of capital.